Sex separation unveils the functional plasticity of the vomeronasal organ in rabbits - Villamayor, Paula R.; Gullón, Julián; Quintela, Luis; Sánchez-Quinteiro, Pablo; Martínez, Paulino; Robledo, Diego (Frontiers in Molecular Neuroscience, 2022)
Chemosensory cues are vital for social and sexual behaviours and are primarily detected and processed by the vomeronasal system (VNS), whose plastic capacity has been investigated in mice. However, studying chemosensory plasticity outside of laboratory conditions may give a more realistic picture of how the VNS adapts to a changing environment. Rabbits are a well-described model of chemocommunication since the discovery of the rabbit mammary pheromone and their vomeronasal organ (VNO) transcriptome was recently characterized, a first step to further study plasticity-mediated transcriptional changes. In this study, we assessed the plastic capacity of the rabbit male and female VNO under sex-separation vs sex-combined scenarios, including adults and juveniles, to determine whether the rabbit VNO is plastic and, if so, whether such plasticity is already established at early stages of life. First, we characterized the number of differentially expressed genes (DEGs) between the VNO of rabbit male and female under sex-separation and compared it to sex-combined individuals, both in adults and juveniles, finding that differences between male and female were larger in a sex-separated scenario. Secondly, we analyzed the number of DEGs between sex-separated and sex-combined scenarios, both in males and females. In adults, both sexes showed a high number of DEGs while in juveniles only females showed differences. Additionally, the vomeronasal receptor genes were strikingly down-regulated in sex-separated adult females, whereas in juveniles up-regulation was shown for the same condition, suggesting a role of VRs in puberty onset. Finally, we described the environment-modulated plastic capacity of genes involved in reproduction, immunity and VNO functional activity, including G-protein coupled receptors. Our results show that sex-separation induces sex- and stage- specific gene expression differences in the VNO of male and female rabbit, both in adults and juveniles. These results bring out for the first time the plastic capacity of the rabbit VNO, supporting its functional adaptation to specifically respond to a continuous changing environment. Finally, species-specific differences and individual variability should always be considered in VNO studies and overall chemocommunication research.